Complementary Therapy of Tui Na Massage Affected the Increase of Children’s Appetite - Lida Khalimatus Sadiya; Veryudha Eka Prameswari; Noer Saudah (Journal of Ners and Midwifery, 2022)
Nutritional status is an indicator in determining a children’s health status. Massage is one of the therapies complementary that many parents choose to avoid malnutrition. Touch therapy (massage) can have positive physical effects, including weight gain. Tui Na massage is a more specific massage technique to overcome feeding difficulties in toddlers by improving blood circulation in the spleen and digestion. The purpose of this study was to measure the extent to which Tui Na massage complementary therapy increased children's appetite.  This research used a literature review design.  The data used secondary data obtained from the results of research that had been carried out by previous researchers whose research journals had been published which were relevant to the topic, from 2015 to 2021, were accessed in full text by 16 journals according to the formulation of the problem and research objectives, and 6 the journal given the Tui Na massage. The results showed that there was an effect of Tui Na massage on weight gain. Tui Na Massage was effective in increasing a toddler's weight. There was an effect of massage on increasing the appetite of toddlers aged 1 year. Based on the results of the above study, the children’s appetite and weight after being given the Tui Na massage treatment, the average growth rate of weight gain increased and the appetite increased above the average of babies who did not get massage treatment.